Mary as Mother of God: Its Implication for the Tradition of the Sisters of Our Lady of Amersfoort in Indonesia - Nanik Wijiyati Aluwesia (P3TK, Sanata Dharma University, 2021)
This article explores the dogma of Mary as Mother of God and its implications in the tradition of the Sisters of Our Lady of Amersfoort (SOLA) in Indonesia. In their traditional prayers to the Blessed Virgin Mary, the SOLA in Indonesia invoke Mary with the title, “Mother of God”. This exploration includes the significance of dogmatic perspective on Mary. What are the implications of the dogma of Mary as Mother of God for the tradition of the Sisters of Our Lady of Amersfoort in Indonesia? Literature study is used as a method in this research. The dogma as Mother of God is reflected in their traditions such as: liturgy, devotion, the motto Tota Christi per Mariam and the formula of their religious vows. Three recommendations are offered: (1) having a uniform structural image of Mary as Mother of God in the Congregations of SOLA; (2) creation of a Marian formation program for all formators of the SOLA and the SOLA in Indonesia, and (3) designing a Marian Formation Program for Junior Sisters, Novices and Postulants, especially the dogma Mary as Mother of God and its implications in the tradition of the Sisters suited to the particular stage of formation.